Trump @ work : really huge lessons on leadership, believe me - Moran, Richard A. (New York, NY : Routledge, 2020)
""Unprecedented" is the adjective most often ascribed to everything about Donald Trump. Trump At Work is about the unprecedented impact that Donald Trump and his Presidency and style has had on attitudes and perceptions of leadership and management. The book brings a unique perspective about what has changed and what has not changed through humorous and true "bullets" and observations. Why do some leaders get fired for things that other leaders boast about? In spite of controversy, why do some initiatives still get implemented? Is implementation all that matters? Is empathy and credibility still critical to success? Why aren't there any instruction manuals about how to navigate the new workplace? These are not questions raised by just a few. These are questions everyone in the workplace is asking. Trump At Work explores these questions and many more. It reveals how the rules of the game have changed for everyone seeking success or at least, to survive. It's hard enough to keep up with leadership and management trends. Donald Trump is making it more difficult, not intentionally, not through the tweets he writes, but by how he is challenging the long existing norms. Who knew that tweeting would become an established way of communicating to an organization? Who knew that in spite of constant searing criticism, one can disregard it and continue to follow an agenda? Who knew that preaching to supporters and ignoring naysayers is a way to manage? Whether you appreciate Donald Trump or not, he has had an impact on the thinking about leadership and management and the author precisely explores that impact in this book"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Trump, Donald, -- 1946-; Leadership -- Moral and ethical aspects; Management -- Moral and ethical aspects; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership